Leadership Influence and Work Environment on Employee Effectiveness in Capital Investment and Integrated Services in One Door City of Gorontalo - Aneta, Yanti; Turtono, Bondan (AIBPM Publisher, 2019)
This study aims to determine the magnitude of the influence of leadership, and the work environment on the work effectiveness of employees in the Gorontalo City Investment and Integrated One-Stop Service. The research approach used is quantitative methods. Sources of data in this study are primary data that is carried out using questionnaires on respondents who have met the standards of the study sample. The data analysis technique used is multiple regression analysis using SPSS program assistance. The results of the study show that (1) Leadership has a positive but not significant effect on the effectiveness of employees in Gorontalo Investment and One-Stop Services in the City of Gorontalo. This is because based on the results of the descriptive analysis shows that the Leadership variable lies in the criteria that are